The efficiency of radiation shielding made from materials with high atomic number and low mass density - Rudychev, V.G.; Azarenkov, M.O.; Girka, I.O.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2021)
The radiation shielding from γ-quanta of the existing transport containers (TC) for transportation of spent nuclear fuel (SNF) is made of steel or steel plus Pb 25…30 cm thick and weighting ⁓ 60…80 t. The application of materials with high atomic number, dispersed (solids grinded to a powdery state) to the densities in the range 4 < ρ < 8 g/cm³, is investigated. Simulations based on the Monte Carlo method show that at the densities of dispersed depleted U larger than 5 g/cm³ and shielding thicknesses of more than 30 cm, the absorption of γ-quanta of SNF is greater than that of the shielding made of steel of the same thickness. The application of such materials, while the weight characteristics of the shields are not exceeded, provides radiation shielding for SNF with the high burnup rate and the smaller cooling time or larger amount of the transported SNF.